Sinemada folklorik korku bağlamında cadı kültüne bakış - Altunkurt, Oğuzhan (My University, 2024)
Bu tez çalışması folklorik korku sinemasında cadı figürünün görünümlerini folklorik korkuyu bir alt tür olarak konumlandırarak ortak uylaşımlar çerçevesinde incelemektedir. Sinemada sıklıkla görülen folklorik bir korku figürü olarak cadının bu alt türün filmlerindeki ortaklaştığı ve farklılaştığı noktalar ile folklorik korku filmlerinin bir alt tür olarak ortak uylaşımları bu bağlamda analiz edilmiştir. 2010 yılından sonra folklorik korku filmlerinin üretiminde artış olduğu ve bu filmlerin akademik literatürde görünür ve tartışılır hale geldiği tespit edilmiştir. Bu nedenle çalışmada 2010 yılı sonrası vizyona giren, birbirinden farklı coğrafyalarda geçen ve cadı figürünü içeren dört film tür analizi metoduyla incelenmiştir. Bu filmler yapım sırasına göre analiz edilmiş olup, The Witch: A New England Folktale (2015, Robert Eggers), Hagazussa: A Heathen’s Curse (2017, Almanya, Lukas Feigelfeld), The Medium (2021, Banjong Pisanthanakun) ve You Won’t Be Alone (2022, Goran Stolevski) filmleri örneklem olarak belirlenmiştir. Yapılan incelemelerle birlikte folklorik korku filmlerinin biçimsel ve anlatısal özellikleri ortaya konmuş, cadı figürünün görünümünün bu filmlerde ortaklaştığı ve farklılaştığı noktalar tespit edilmeye çalışılmıştır.

This thesis examines the appearance of the witch figure in folkloric horror cinema by positioning folkloric horror as a subgenre and analyzing commonalities within the framework of folkloric horror. Along with the commonalities of folkloric horror films as a subgenre, the study examines how the witch, a commonly portrayed figure in folkloric horror cinema, shows similarities and divergences in these subgenre films. Since 2010, an increase in the production of folkloric horror films can be observed, resulting in its increasing visibility and scientific discussion in the academic literature. Therefore, the study focuses on four films released after 2010 that set in different geographical locations and featuring the character of the witch, analyzed through the methodology of genre analysis. These films are analyzed in chronological order, including The Witch: A New England Folktale (2015, Robert Eggers), Hagazussa: A Heathen's Curse (2017, Germany, Lukas Feigelfeld), The Medium (2021, Banjong Pisanthanakun), and You Won't Be Alone (2022, Goran Stolevski), selected as representative samples. Through these analyses, the formal and narrative characteristics of folkloric horror films are delineated, while attempting to identify commonalities and differences in how the witch character is portrayed in these films.
Looking at the cult of witchcraft in the context of folkloric horror in cinema
Keywords: Cadılık; Fear in motion pictures; Folk Horror; Folklorik Korku; Genre Analysis; Genre Cinema; Horror Cinema; Horror films; Korku filmleri; Korku Sineması; Korku, Sinemada; Tür Analizi; Tür Sineması; Witchcraft